Visual symbols as a tool of cultural and environmental resistance: the example of the movement "Sakkar al-Siyap" (Close the Siape) of Sfax-Tunisia - Bouthaina Bouallegui; Moncef Gubsi; Ali Elloumi (Journal of Psychology and Social Sciences, 2025)
In the context of the rise of environmental movements and the intensification of popular demonstrations against industrial pollution, visual stimuli have become a central element of the expression of disagreement and the demand for environmental justice. In this context, this article focuses on the analysis of visual symbols within the Sfax movement as an expression of environmental injustice and a mechanism for stimulating collective consciousness. This article is based on social semiotics and Pierre Bourdieu's theory of symbolic power to deconstruct the relationship between the signifier and the social and political signifier.ّ shows how resistance is embodied through the image, because it is loaded with deep cultural connotations and anchored in the context. In this context, the visual symbol is not only seen but also felt as an act of resistance.